Symmetry and Asymmetry of World Oil Prices Against Major World Stock Indices - Wina Nurfitriani (SINTESA, 2022)
This research was conducted to examine the effect of changes in oil prices on stock returns in the largest commodity-producing countries and the largest oil-importing countries, namely America, China, India and Indonesia. The research period was carried out during a decline in the stock market in 2022 (January 2022 – October 2022). The research method used was quantile regression, where the results show different symmetric and asymmetric effects in each country. The negative and significant effects of oil prices and stock returns occur in India, while the positive and significant effects occur in the United States and Indonesia. For China, no significant evidence was found between the influence of oil prices and stock returns even though China is one of the largest oil producers.